Professional image creation by students on social media sites (in the light of empirical research) = Kreowanie wizerunku zawodowego przez studentów w serwisach społecznościowych (w świetle badań empirycznych) - Stankiewicz, Janina; Bortnowska, Hanna (Zielona Góra: Faculty of Economics and Management Press)
Internet has become an important way of our image creation, including the professional one. By participating in social media, is possible to shape our own image not only in eyes of private persons, but also of potential employers. The aim of the article is to identify activities which were undertaken by young participants in labour market (students) associated with creating their own professional image in social media.
Keywords: wizerunek zawodowy; serwisy społecznościowe; internet; kariera zawodowa; badania empiryczne; professional image; social media; career; empirical research